Examination of how food environment and psychological factors interact in their relationship with dietary behaviours: test of a cross-sectional model - Christina Vogel; Gavin Abbott; Georgia Ntani; Mary Barker; Cyrus Cooper; Graham Moon; Kylie Ball; Janis Baird (BMC, 2019)
Abstract Background To improve population diet environmental strategies have been hailed the panacea because they require little agency or investment of personal resources; this contrasts with conventional strategies that rely on individuals to engage high levels of agency and make deliberate choices. There is an immediate need to improve understanding of the synergy between the psychological and environmental determinants of diet in order to optimise allocation of precious public health resources. This study examined the synergistic and relative association between a number of food environment and psychological factors and the dietary behaviours of a population sample of women with young children. Methods Women in Hampshire were recruited from children's centres and asked about their demographic characteristics, psychological resources, dietary behaviours (food frequency questionnaire) and perceptions of healthy food access and affordability. Three local food environment factors were objectively assessed: i) spatial access to food outlets using activity spaces; ii) healthfulness of the supermarket where women did their main food shop, (based on nine in-store factors including price, placement and promotion on seven healthy and five less healthy foods); iii) nutrition environment of children's centres visited frequently by the women, assessed via staff-administered questionnaire. A theoretical model linking environmental factors to dietary behaviours, both directly and indirectly through three factors representing individual agency (psychological resources, perceived food affordability, perceived food accessibility), was tested using Structural Equation Modelling. Results Complete data were available for 753 women. The environment of women's main supermarket was indirectly related to their dietary behaviours through psychological resources and perceived food affordability. Shopping at supermarkets classified as having a healthier in-store environment was associated with having greater psychological resources associated with healthy eating (standardised regression weight β = 0.14SD, p = 0.03) and fewer food affordability concerns (β = − 0.14SD, p = 0.01), which in turn related to healthier dietary behaviours (β = 0.55SD, < 0.001 and β = − 0.15, p = 0.01 respectively). The three food environment factors were not directly associated with dietary behaviour (p > 0.3). The overall model fit was good (CFI = 0.91, RMSEA = 0.05 [0.05, 0.06]). Conclusions This pathway analysis identified three focal points for intervention and suggests that high-agency interventions targeting individual psychological resources when combined with low-agency supermarket environment interventions may confer greater benefits on dietary behaviours than either intervention alone.